"Den du bråkar med är du kär i" : En kvalitativ intervjustudie av kuratorers perspektiv på sexuella trakasserier i skolan - Thomée,Mimmi; Löf,Josefine (2018)
“The one you mess with is the one you like”. A qualitative interview study on school counsellors perspectives on sexual harassment in school. The aim of this study was to investigate school counsellor's perspectives on sexual harassment by looking at how school counsellors describe sexual harassment in their schools, how they describe the cause of the problem in their school and how they think they and their school should work with the problem.The method we used was qualitative and semi structured interviews with six school counsellors working at different levels of school in a bigger city in Sweden. The theoretical frame of the study was problem perspective, gender theory/performativity and intersectionality. The study found that the school counsellors have different perspectives on the problem and that this perspective is build up by different components, such as what reasons they find to explain the problem, how much they see sexual harassment as a problem in their school, how they work with the question and think that the problem should be worked with. These component are in some of the perspectives related to each other and in some perspectives not as much. The study further found that the school counsellors thought that the preventive work is the most relevant work when it comes to working with inequality and sexual harassment and that sexual harassment still is a hidden problem, although the #metoo campaign has made it more visual in the society.
Keywords: School counsellors; Sexual harassments; Student health; Preventive work; Problem perspective